Should IVF be used as first-line treatment or as a last resort? A debate presented at the 2013 Canadian Fertility and Andrology Society meeting. Issue 2 (February 2015) - Huang, Lina N.; Tan, Justin; Hitkari, Jason; Dahan, Michael H.
Abstract: Infertility outcomes can be influenced by many factors. Although a number of treatments are offered, deciding which one to use first is a controversial topic. Although IVF may have superior efficacy in achieving a live birth with a reasonable safety profile, the availability of cheaper and less invasive treatments preclude its absolute use. For this reason, certain patient groups with 'good-prognosis' infertility are traditionally treated with less invasive treatments first. 'Good-prognosis' infertility may include unexplained infertility, mild male factor infertility, stage I or II endometriosis, unilateral tubal blockage and diminished ovarian reserve. Here, evidence behind the use of IVF as a first-line treatment is compared with its use as a last-resort option in women with 'good-prognosis' infertility.